Visualizing Truth in Digital Conflicts: Fact-Checking as Image Governance in Contested Information Spaces (Architecture Image Studies, 2026)
In contemporary digital conflicts, images function not merely as communicative content but as architectural structures of meaning that organize perception, affect, and political positioning within information spaces. Visual misinformation—through decontextualized photographs, altered screenshots, memes, and video fragments—operates by destabilizing the spatial and semiotic coherence of these environments. While existing scholarship has extensively examined fact-checking as an epistemic or journalistic corrective, its role as a visual-governance practice remains underexplored. This article reconceptualizes fact-checking as a form of image governance that intervenes in the circulation, spatial positioning, and symbolic stabilization of visual meaning in conflict-laden digital environments. Drawing on qualitative visual analysis of approximately twenty-five image-centered fact-checking reports published between 2020 and 2023 by international and Indonesian platforms, the study examines how misleading visuals are dismantled, recontextualized, and architecturally reassembled. The analysis identifies three recurring modes of visual governance: visual deconstruction, contextual re-anchoring, and symbolic repair. By situating fact-checking within image studies, visual culture, and spatial theories of digital media, this article advances an interdisciplinary understanding of how visual meaning is governed in contested information architectures. The findings suggest that fact-checking operates not only at the level of factual verification but as a culturally situated practice of representational re-architecture, essential for maintaining visual coherence and mitigating conflict escalation in contemporary digital spaces.